2014
DOI: 10.1182/blood-2013-12-544221
|View full text |Cite
|
Sign up to set email alerts
|

Echinomycin protects mice against relapsed acute myeloid leukemia without adverse effect on hematopoietic stem cells

Abstract: • Echinomycin can selectively kill the leukemia-initiating cell in relapsed AML without normal stem cell toxicity.• In vivo delivery of echinomycin can induce long-term complete remission in a murine model of relapsed AML.Acute myeloid leukemia (AML) often relapses following chemotherapy-induced remission and is generally chemo-resistant. Given the potential role for cancer stem cells in relapse, targeting of the leukemia-initiating cell (LIC) in AML may provide improved outcome following remission induction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 48 publications
4
56
1
Order By: Relevance
“…Furthermore, our data indicating that HIF-1α is a main player in the hypoxia-mediated control of miR-146a and CXCR4 support the findings of previous studies 24,25 that used chemotherapy and HIF-inhibitors in combination to restore the drug sensitivity of leukemic cells in hypoxia, indicating a new therapeutic possibility to decrease leukemic cell resistance to cytotoxic drug treatment. Wang et al showed that HIF-1α is constitutively expressed in enriched populations of leukemic stem cells purified from AML, and its targeting eliminates these cells.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, our data indicating that HIF-1α is a main player in the hypoxia-mediated control of miR-146a and CXCR4 support the findings of previous studies 24,25 that used chemotherapy and HIF-inhibitors in combination to restore the drug sensitivity of leukemic cells in hypoxia, indicating a new therapeutic possibility to decrease leukemic cell resistance to cytotoxic drug treatment. Wang et al showed that HIF-1α is constitutively expressed in enriched populations of leukemic stem cells purified from AML, and its targeting eliminates these cells.…”
supporting
confidence: 89%
“…21,22 The use of HIF inhibitors represents a new strategy for the development of therapies targeting the hypoxic cancer microenvironment. [23][24][25][26][27] Stabilization of HIF proteins by dimethyloxalyl glycine treatment, increases hematopoietic stem cell quiescence in vivo, improves blood recovery and enhances hematopoietic stem cell survival in the bone marrow of irradiated mice. 23 Echinomycin, a DNA-intercalating agent that blocks HIF DNA-binding activity, selectively eradicates cancer stem cells in mouse models of lymphoma and human AML 24 and selectively kills leukemia-initiating cells, inducing long-term remission in a murine model of relapsed AML.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Echinomycin has no impact on selfrenewal and differentiation of HSCs, which makes it a perfect drug to eradicate leukemia. 58 Another well-known drug, L-ascorbic acid in high concentrations, has also been shown to inhibit the expression of HIF-1α in CML cells. It is particularly important in CML treatment to find a molecule capable of impacting LSCs that are completely resistant to TKI-based modalities.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%